The Challenges of Educators in Post-Pandemic Moral Improvement - Muhammad Rasyid Ridho (Universitas Muhammadiyah Yogyakarta, 2023)
The current situation and condition of the Covid-19 pandemic has affected the system of human life, especially in the education sector. Education that was initially carried out with a learning system in schools had to change to an online learning system. Online learning actually makes students or students experience a moral decline caused because educators cannot provide moral education directly. In the learning that is carried out, educators are more inclined to the success or achievement of subjects, resulting in the absence of moral education. This study aims to find out what moral education is, the urgency of post-pandemic moral education and an analysis of educators' challenges in moral improvement after the pandemic. In this research method uses a qualitative method with a literature review approach. The data obtained from this research is through reference books, journals, and previous research that has a relationship with what the author is doing